The short history of Hungarian sheep breeding and Hungarian merino breed - Nagy, Zsuzsanna; Németh, Attila; Mihályfi, Sándor; Toldi, Gyula; Gergátz, Elemér; Holló, István (Acta Agraria Kaposváriensis, 2011)
The aim of this study was to show the situation of Hungarian sheep breeding, and the evolution of Hungarian merino sheep breed from the starts to nowdays. In spite of the depreciation of wool, the Merino sheep stock has a 80% part of the whole Hungarian sheep flock. The sector produces mostly only one product for one foreign market. The main product is the exported lamb, also has shown a significant decrease last years, got mostly (90%) to Italy. As a result of the above-mentioned facts, the meat production of Merino sheep has came to the front last years. The rate of sold lambs per ewe (70%), the average daily weight gain of lambs (250 gr/day) are showing a low level of production.
Keywords: sheep; hungarian merino; Hungarian sheep breeding